SIDS Sudden infant and early childhood death The past, the present and the future - Duncan, Jhodie R (University of Adelaide Press, 2018)
This volume covers aspects of sudden infant and early childhood death, ranging from issues with parental grief, to the most recent theories of brainstem neurotransmitters. It also deals with the changes that have occurred over time with the definitions of SIDS (sudden infant death syndrome), SUDI (sudden unexpected death in infancy) and SUDIC (sudden unexpected death in childhood). The text will be indispensable for SIDS researchers, SIDS organisations, paediatric pathologists, forensic pathologists, paediatricians and families, in addition to residents in training programs that involve paediatrics. It will also be of use to other physicians, lawyers and law enforcement officials who deal with these cases, and should be a useful addition to all medical examiner/forensic, paediatric and pathology departments, hospital and university libraries on a global scale. Given the marked changes that have occurred in the epidemiology and understanding of SIDS and sudden death in the very young over the past decade, a text such as this is very timely and is also urgently needed.